Identification of Novel Targets of RBM5 in the Healthy and Injured Brain. (1st August 2020) - Jackson, Travis C.; Janesko-Feldman, Keri; Gorse, Kiersten; Vagni, Vincent A.; Jackson, Edwin K.; Kochanek, Patrick M.
Highlights: In vivo elucidation of mRNA targets regulated by RBM5 in the brain. RBM5 KO increases total levels of Rims2 transcripts in the cerebellum. RBM5 KO increases Rims2 splicing in the cortex and in the hippocampus. Csnka2ip mRNA is expressed in the mammalian brain. RBM5 KO increases total levels of Csnka2ip mRNA in the cortex. Abstract: The tumor suppressor RNA-binding motif 5 (RBM5) regulates the expression levels and cassette exon-definition (i.e. splicing) of a select set of mRNAs in a tissue-specific manner. Most RBM5-regulated targets were identified in oncological investigations and frequently involve genes which mediate apoptotic cell death. Little is known about the role of RBM5 in the brain. Also, it is unclear if a brain injury may be required to detect RBM5 mediated effects on pro-apoptotic genes due to their low expression levels in the healthy adult CNS at baseline. Conditional/floxed (brain-specific) gene deleter mice were generated to elucidate CNS-specific RBM5 mRNA targets. Male/female mice were subjected to a severe controlled cortical impact (CCI) traumatic brain injury (TBI) in order to increase the background expression of pro-death mRNAs and facilitate testing of the hypothesis that RBM5 inhibition decreases post-injury upregulation of caspases/FAS in the CNS. As expected, a CCI increased caspases/FAS mRNA in the injured cortex. RBM5 KO did not affect their levels or splicing. Surprisingly, KO increased the mRNA levels of novel targets including casein kinase 2 alpha prime interacting protein (Csnka2ip/CKT2) – a gene not thought to be expressed in the brain, contrary to findings here. Twenty-two unique splicing events were also detected in KOs including increased block-inclusion of cassette exons 20–22 in regulating synaptic membrane exocytosis 2 (Rims2). In conclusion, here we used genome-wide transcriptomic analysis on healthy and injured RBM5 KO mouse brain tissue to elucidate the first known gene targets of this enigmatic RBP in this CNS.